Risk of thyroid as a first or second primary cancer. A population‐based study in Italy, 1998–2012. (17th September 2021) - Crocetti, Emanuele; Mattioli, Veronica; Buzzoni, Carlotta; Franceschi, Silvia; Serraino, Diego; Vaccarella, Salvatore; Ferretti, Stefano; Busco, Susanna; Fedeli, Ugo; Varvarà, Massimo; Falcini, Fabio; Zorzi, Manuel; et al.
Abstract: Background: The number of patients living after a cancer diagnosis is increasing, especially after thyroid cancer (TC). This study aims at evaluating both the risk of a second primary cancer (SPC) in TC patients and the risk of TC as a SPC. Methods: We analyzed two population‐based cohorts of individuals with TC or other neoplasms diagnosed between 1998 and 2012, in 28 Italian areas covered by population‐based cancer registries. Standardized incidence ratios (SIRs) of SPC were stratified by sex, age, and time since first cancer. Results: A total of 38, 535 TC patients and 1, 329, 624 patients with other primary cancers were included. The overall SIR was 1.16 (95% CI: 1.12–1.21) for SPC in TC patients, though no increase was shown for people with follicular (1.06) and medullary (0.95) TC. SPC with significantly increased SIRs was bone/soft tissue (2.0), breast (1.2), prostate (1.4), kidney (2.2), and hemolymphopoietic (1.4) cancers. The overall SIR for TC as a SPC was 1.49 (95% CI: 1.42–1.55), similar for all TC subtypes, and it was significantly increased for people diagnosed with head and neck (2.1), colon–rectum (1.4), lung (1.8), melanoma (2.0), bone/soft tissue (2.8), breast (1.3), corpus uteri (1.4), prostate (1.5), kidney (3.2), central nervous system (2.3), and hemolymphopoietic (1.8) cancers. Conclusions: The increased risk of TC after many other neoplasms and of few SPC after TC questions the best way to follow‐up cancer patients, avoiding overdiagnosis and overtreatment for TC and, possibly, for other malignancies. Abstract : This is the first study able to calculate population‐based risk of thyroid cancers as a first or second tumor separately for different thyroid cancer histological types (i.e., follicular, medullary, and poorly differentiated). In a context of a large proportion of thyroid cancer cases due to overdiagnosis, the findings of the present study may help to more focused primary prevention and surveillance for side effects of treatments, thus avoiding overtreatment, particularly among younger women.